Dean Reed; (1973)
Seite 1:<NZ>1. We are the revolutionaries<NZ>2. Things I have seen<NZ>3. Immer lebe die Sonne<NZ>4. Guantanamera<NZ>5. We shall overcome<NZ>6. Caminando e cantando<NZ>7. Glory Hallelujah<NZ><NZ>Seite 2:<NZ>8. Eloise<NZ>9. I did it my way<NZ>10. Love resister<NZ>11. Softly<NZ>12. Mississippi-Line<NZ>13. Yesterday when I was young<NZ>14. Non e la Pioggia<NZ>15. Hemos dicho basta<NZ>16. Maria;